2015
DOI: 10.1103/physrevb.92.104418
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of the exchange interactions in Gd-doped GaN containing N interstitials, O interstitials, or Ga vacancies

Abstract: Using large supercells models and the KKRnano multiple scattering approach, statistically meaningful information is obtained on the distribution of local densities of states, magnetic moments and distance dependent exchange interactions for interstitial N or O or Ga-vacancies in Gd-doped GaN. The exchange interactions between N-interstitials (Ni) and Ni with Gd are found to be shortranged and mainly antiferromagnetic, while exchange interactions between Gd are negligible. For O-interstitials, the ferro-and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 38 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…45 Furthermore, Thiess et al proposed that the Ga vacancies provide significantly strong and robust ferromagnetic interactions between spins that are localized on the nitrogen near the vacancies. 46,47 Eu-doped GaN may also be affected by such native defects like Ga vacancies. We will focus on such effect in future studies.…”
Section: A General Form Of the Hamiltonian Of The Heisenberg Model Ismentioning
confidence: 99%
“…45 Furthermore, Thiess et al proposed that the Ga vacancies provide significantly strong and robust ferromagnetic interactions between spins that are localized on the nitrogen near the vacancies. 46,47 Eu-doped GaN may also be affected by such native defects like Ga vacancies. We will focus on such effect in future studies.…”
Section: A General Form Of the Hamiltonian Of The Heisenberg Model Ismentioning
confidence: 99%
“…However, the microscopic origin of the defects and their involvement in establishing long range magnetic ordering is still unclear. Theoretical studies have shown that certain defects, such as Ga-vacancies(V Ga ), [15][16][17][18] 19 as well as nitrogen vacancy(V N )-Ga vacancy complexes 20,21 , which possess magnetic moment, can account for the large effective magnetic moment per Gd ion and explain ferromagnetism in this material. It is noteworthy that ferromagnetism above room temperature has been observed in semiconductors such as HfO, ZnO, TiO 2 , In 2 O 3 , where atoms with partially filled d or f shells are not present at all 22 .…”
mentioning
confidence: 99%